2015
DOI: 10.1155/2015/697275
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Short Sleep and Shift Work Status with Hypertension among Black and White Americans

Abstract: Objective. The purpose of this study was to investigate whether short sleepers (<6 hrs) who worked the non-day-shift were at greater likelihood of reporting hypertension and if these associations varied by individuals' ethnicity. Methods. Analysis was based on the 2010 National Health Interview Survey (NHIS). A total of 59,199 American adults provided valid data for the present analyses (mean age = 46.2 ± 17.7 years; 51.5% were female). Respondents provided work schedule and estimated habitual sleep durations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…The alleged reduction in associated risk of incident stroke among black adults with short sleep duration, particularly black men, is perplexing, and conflicts with other studies examining race by sleep interactions on cardiometabolic risk factors. Most previous cross-sectional, nationally based cohort studies have found that short sleep duration was associated with prevalent hypertension (self-reported), 16,18 hypercholesteremia, 17 obesity, 16 and diabetes 14 among black adults but not white adults, with only one exception, when the opposite was found. 19 However, these cross-sectional studies cannot inform about possible explanatory pathways.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The alleged reduction in associated risk of incident stroke among black adults with short sleep duration, particularly black men, is perplexing, and conflicts with other studies examining race by sleep interactions on cardiometabolic risk factors. Most previous cross-sectional, nationally based cohort studies have found that short sleep duration was associated with prevalent hypertension (self-reported), 16,18 hypercholesteremia, 17 obesity, 16 and diabetes 14 among black adults but not white adults, with only one exception, when the opposite was found. 19 However, these cross-sectional studies cannot inform about possible explanatory pathways.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous work suggested that short sleep duration partially mediated the relationship between race (black vs white adults) and incident stroke symptoms, 13 and other studies also suggest that short or long sleep duration may be associated with excess risk for poor cardiometabolic risk status among black adults. [14][15][16][17][18][19] However, studies addressing black-white differences on the influence of sleep duration on incident stroke are rare.…”
mentioning
confidence: 99%
“…This inconsistency may be explained by the limited number of participants in the current study, resulting in a greater degree of variation in blood pressure measurements. The findings of an additional American study, however, were limited to an association between sleep duration and blood pressure in African-American shift workers [ 29 ]. Other studies with contrasting findings are also available.…”
Section: Discussionmentioning
confidence: 99%
“…Un pequeño porcentaje de los estudios seleccionados busca encontrar una asociación entre el turno laboral y los cambios en parámetros del cortisol y melatonina, así como el ciclo de sueño/vigilia (25)(26) . Es persistente el resultado de un cambio del patrón diurno de melatonina y cortisol en los participantes que se desempeñan en el turno nocturno o rotatorio, caracterizado por un aumento de la secreción de cortisol lo cual a su vez está relacionado con múltiples alteraciones metabólicas como la hipertensión (27) y el sobrepeso (28) . Esto aunado a el estrés y la depresión que según estudios se muestran como factores de riesgo a la salud en trabajadores nocturnos (29) .…”
Section: Discussionunclassified